Micro-Place Homicide Patterns in Chicago 1965 - 2017 - Wheeler, Andrew P.; Herrmann, Christopher R.; Block, Richard L. (Springer International Publishing, 2021)
This brief examines 36,263 homicides in Chicago over a 53-year study period, 1965 through 2017, at micro place grid cells of 150 by 150 meters. This study shows not only long-term historical patterns of homicides in Chicago, but also places that historical context of homicide in reference to the dramatic increases in homicides in 2016-2017. It uses several different inequality metrics, as well as kernel density maps to demonstrate that homicides were more clustered in the 1960's compared to later periods. Using zero inflated group-based trajectory models, it demonstrates the long-term temporal stability of homicides at micro places. This brief will be of interest to researchers in policing, homicide, and research methods in criminology. Analyzes homicides in Chicago over a 50-year period in micro place grid cells; Displays long-term patterns of homicides in Chicago, placed in historical context; Uses micro-place grid cells and quantitative research methods to demonstrate trajectories of homicides in Chicago
Keywords: Policing; Research Methods in Criminology; Police; Criminology; Research